2014
DOI: 10.3329/bjp.v9i1.17337
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity of aqueous methanolic extract of <i>Morus nigra</i> against paracetamol-induced hepatotoxicity in mice

Abstract: Morus nigra (Family Moraceae) is traditionally used injaundice, diabetes, hypertension, cough, fever and cancer. The current study was conducted to determine hepatoprotective activity of aqueous methanolic extract of leaves of M. nigra. Two doses of 250 mg/kg p.o and 500 mg/kg p.o showed that extract of M. nigra produced significant (p<0.001) reduction in liver enzymes (ALT, AST, ALP) and total bilirubin induced by paracetamol and the results are comparable to silymarin (p<0.001). Results were supported by his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 24 publications
(26 reference statements)
1
28
0
1
Order By: Relevance
“…Additionally, Araújo et al (2015) demonstrated an increased insulinemia and improved oxidative stress state in diabetic rats treated with hydroethanolic leaf extract. Morus nigra leaves have shown evidence of antiinflammatory, antinociceptive and hepatoprotective effects (Padilha et al 2009, Malhi et al 2014. Although, Queiroz et al (2012), did not confirmed the estrogenic activity, the most popular use of M. nigra.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, Araújo et al (2015) demonstrated an increased insulinemia and improved oxidative stress state in diabetic rats treated with hydroethanolic leaf extract. Morus nigra leaves have shown evidence of antiinflammatory, antinociceptive and hepatoprotective effects (Padilha et al 2009, Malhi et al 2014. Although, Queiroz et al (2012), did not confirmed the estrogenic activity, the most popular use of M. nigra.…”
Section: Introductionmentioning
confidence: 92%
“…Recent studies developed by Memon et al (2010), Malhi et al (2014), Araújo et al (2015), Sánchez-Salcedo et al (2015) with black mulberry leaves extracts using organic solvents demonstrated the richness of phenolic compounds which provides a potential antioxidant activity. Since oxidative stress has been implicating on the improvement of cardiovascular and neurodegenerative diseases this source of phenolics could be usefull therapy (Heo and Lee 2006, Tarozzi et al 2013, Wiczkowski et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…However, now-a-days, the trend is also being changed to the use of herbal products or extracts to control the diseases. The plant kingdom still holds many species containing substances of medicinal value which have yet to be discovered: large numbers of plants are constantly being screened for their possible pharmacological value particularly for their anti-inflammatory , hypotensive (Qadir, 2010), hepatoprotective (Ali et al, 2013;Mallhi et al, 2014;Saleem et al, 2014a;, hypoglycemic, amebicidal, anti-fertility, cytotoxic, antibiotic (Amin et al, 2012), Spasmolytic, bronchodilator, anti-oxidant and anti-parkinsonism properties.…”
Section: Introductionmentioning
confidence: 99%
“…Bố trí thí nghiệm như sau: 30 chuột được chia làm 5 lô (6 chuột/lô). (i) Lô 1 (đối chứng sinh lí): uống nước cất 0,2 ml/con/ngày; (ii) Lô 2 (đối chứng bệnh lí): uống nước cất và uống paracetamol; (iii) Lô 3: uống cao methanol Xáo tam phân, liều 10 g/kg thể trọng (kgP)/ngày và uống paracetamol; (iv) Lô 4: uống cao nước Xáo tam phân, liều 10 g/kgP/ngày và uống paracetamol; (v) Lô 5 (đối chứng tham khảo): uống silymarin liều 50 mg/kgP/ngày [13] và uống paracetamol.…”
Section: Phương Pháp Nghiên Cứu Tác Dụng Bảo Vệ Gan Của Cao Chiết Trêunclassified